2011
DOI: 10.1111/j.1755-5922.2011.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilates in Heart Failure Patients: A Randomized Controlled Pilot Trial

Abstract: Background: Conventional cardiac rehabilitation program consist of 15 min of warmup, 30 min of aerobic exercise and followed by 15 min calisthenics exercise. The Pilates method has been increasingly applied for its therapeutic benefits, however little scientific evidence supports or rebukes its use as a treatment in patients with heart failure (HF). Purpose: Investigate the effects of Pilates on exercise capacity variables in HF. Methods: Sixteen pts with HF, left ventricular ejection fraction 27 ± 14%, NYHA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 33 publications
3
31
0
9
Order By: Relevance
“…Many studies have observed a decrease on blood pressure after a period of resistance exercise training [31][32][33][34][35]. In the present study, to our knowledge, we observed for the first time a significant decrease on BP and DP at rest in hypertensive women who participated in MP training.…”
Section: Discussionsupporting
confidence: 38%
“…Many studies have observed a decrease on blood pressure after a period of resistance exercise training [31][32][33][34][35]. In the present study, to our knowledge, we observed for the first time a significant decrease on BP and DP at rest in hypertensive women who participated in MP training.…”
Section: Discussionsupporting
confidence: 38%
“…Estudo no nosso meio demonstrou que a idade não influencia a resposta ao exercício 69 . Outros métodos de treinamento têm sido utilizados como o treinamento complementar de músculos inspiratórios que pode ser indicado naqueles pacientes com IC que apresentam fraqueza da musculatura respiratória (> 70% da pressão inspiratória máxima predita) [70][71][72] ; pilates 73,74 ; treino intervalado e contínuo 66,75,76 ; eletroestimulação 77 ; e hidroterapia 78,79 . Intensidades diferentes de exercício podem ter ação diferente na fisiopatologia da IC 80 .…”
Section: Reabilitação E Treinamento Físico (Tabela 10)unclassified
“…Os programas de reabilitação cardíaca reduzem a morbidade e a mortalidade de coronariopatas 1,5 . No entanto, existe dificuldade em manter o entusiasmo dos pacientes, visando à aderência ao tratamento 6,7 , tornando necessárias novas estratégias, o que tem motivado pesquisas no Brasil e no exterior [8][9][10] . Nesse contexto, a dança configura-se como alternativa eficaz 11,12 , sendo uma atividade lúdica e prazerosa, capaz de proporcionar motivação para realização de atividades físicas 13 , beneficiar os aspectos social, emocional e cognitivo, comprovadamente melhorando a capacidade física e a qualidade de vida (QV) de indivíduos saudáveis 14,15 , já sendo utilizada na recuperação de pacientes com doenças crônicas não transmissíveis 11,12,[16][17][18] .…”
Section: Introductionunclassified